Abin Arab and the sufism (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Sufism is a science intended to purification the souls and clean heart and reforming morality and access to the rank of charity . This science has been fought by some groups to destroy the spirit of Islam and its orientation to the problems that have sought to destroy the moderate tolerant Islam, and not just as ideology but fought its statesmen who have previous publication of religious philosophy and social tolerance, especially Aben Arabe , the philosopher , who the world could not be enough to his ideas ,theories , writings and his trips that require volumes to talk about . Despite the greatness of this scientist a group of opponents ,who accused him of blasphemy outright from which so innocent, emerged . So they took up his ideas and texts on the face of it without standing on the essence of what he meant or wanted .